Evaluation of Salivary Leptin Levels in Healthy Subjects and Patients with Advanced Periodontitis - Afshin Khorsand; Mojtaba Bayani; Siamak Yaghobee; Sepehr Torabi; Mohammad Javad Kharrazifard; Fatemeh Mohammadnejhad (Tehran University of Medical Sciences, 2016)
Objectives: Leptin is a hormone-like protein produced by the adipose tissue. It plays an important role in protection of host against inflammation and infection. Some studies have reported changes in leptin levels in the gingival crevicular fluid (GCF), saliva and blood serum of patients with periodontal disease compared to healthy individuals. The aim of the present study was to compare the salivary leptin levels in patients with advanced periodontitis and healthy individuals. Materials and Methods: In this case-control study, the salivary samples of healthy individuals and patients with advanced periodontitis with clinical attachment loss >5mm were obtained using a standardized method and the leptin levels were measured in the salivary samples by means of ELISA. The effects of the periodontal status and sex on the salivary leptin levels of both groups were statistically analyzed by two-way ANOVA. Results: The means ± standard deviation (SD) of salivary leptin levels in healthy subjects and patients with advanced periodontitis were 34.27±6.88 and 17.87±5.89 pg/mL, respectively. Statistical analysis showed that the effect of sex on the salivary leptin levels was not significant (P=0.91), while the effect of advanced periodontitis on the salivary leptin levels was significant compared to healthy individuals (P<0.0001). Conclusions: In patients with advanced periodontitis, the salivary leptin levels were significantly lower compared to healthy individuals. Thus, assessment of salivary leptin can be done as a non-invasive and simple method to determine the susceptibility of patients to advanced periodontitis.